PENERAPAN BRANDING PADA UKM MAKANAN RINGAN DI KABUPATEN JEPARA - Hari Susanta Nugraha; Fitrie Ariyanti; Dar wanto (Jurnal Administrasi Bisnis, 2017)
The implementation of branding to SME’s products can help the consumers to choose products from the competitors. The emergence of branding on SME’s products cause by the needed of identity for product’s of SME’s for entering in the national market, thus increasing penetration. In fact, many SMEs are not yet aware of the importance of branding for competitiveness. The SME’s are more focused on aspects of product sales. The purpose of the study is that known the business conditions and application of branding of SME’s snacks in Jepara District. The research used qualitative approach to disclusore the emergence of branding. The implementation of branding to SME’s focus on desgn of packaging and labeling. Packaging with attractive designs and informative labels can determine the consumer's interest in purchasing the product. The more familiar a product, the easier it will be for market to choose.